Penyuluhan Hukum Peningkatan Pemahaman Tentang Pentingnya Surat Ijin Penangkapan Ikan bagi Nelayan di Desa Dharma Tanjung, Kecamatan Camplong, Kabupaten Sampang - Indah Cahyani; Moh. Soleh; Abd. Wachid Habibullah; Achmad Muafa; Muh. Urib Abdullah; Prihati Setya Ningsih; Suci Kriswahyun (Nusantara Mengabdi Kepada Negeri, 2025)
Fishing licence (SIPI) is one of the things that must be owned by fishermen in fishing in Indonesian waters. In Article 27 paragraph (1) of Law Number 45 of 2009 concerning Fisheries, it is stated that every person who owns and/or operates an Indonesian-flagged fishing vessel used for fishing in the fisheries management area of the Republic of Indonesia and/or the high seas must have a SIPI.Dharma Tanjung Village, Camplong Subdistrict is one of the fisheries areas among the fisheries areas on Madura Island, the people in Camplong Subdistrict are known for their profession as fishermen, especially in Tanjung Village and Pandian Village. The fishing gear used are gill nets and traditional fishing rods and the factors that are thought to affect fishing production using gill net boats are fishing trips, ship engine size, amount of fuel, size of fishing gear and labour and the biggest influencing factor is the trawl gear used by fishermen in Tanjung Village. Many fishermen of Dharma Tanjung Village, Sampang who have ships with a size of 5 gross tonnes still do not have SIPI. so it is necessary to have counselling about the importance of fishermen to have SIPI.